A Trump doctrine? unpredictability and foreign policy - Bentley, Michelle; Lerner, Adam B. (Routledge, Taylor & Francis Group, 2023)
US President Donald Trump’s foreign policy doctrine is the subject of vast debate. Analysts and practitioners routinely disagree as to what ideology and thinking informed his foreign policy approach – and even whether Trump was politically capable of formulating a doctrine at all. This book explores one specific line of analysis, which deals with the concept of what has been termed the ‘doctrine of unpredictability’. Trump has repeatedly declared that being unpredictable comprises the ideal approach to foreign policy for a state leader. Never be predictable; never let others know what you will do next. The contributors to this volume consider whether a conception of unpredictability did inform Trump’s foreign policy as a coherent doctrine. Yet this book also takes the issue further to problematize what the very concept of unpredictability means in respect to International Relations. What is unpredictability – and how does the concept apply in respect to Trump especially? What impact does unpredictability have on international relationships? How far does unpredictability deviate from previous approaches to foreign policy, not least Madman Theory? And is it even possible to understand the idea of unpredictability fully within a discipline that is more typically committed to comprehending certainty in respect to international politics?
The chapters in this book were originally published as a special issue of 'Cambridge review of international affairs' (volume 34, issue 3)
Keywords: Trump, Donald / 1946-; United States / Foreign relations / 2017-2021; Diplomatic relations; United States; 2017-2021